AN EARLY EXPERIMENT OF MODERN HUNTING OF WHALES IN MAGALLANES: THE STEAMBOAT MAGALLANES OF THE BRAUN & BLANCHARD AND CAPTAIN ANDRESEN - Quiroz, Daniel; Mayorga Zuñiga, Marcelo Paolo (My University, 2018)
In this paper we study a whaling experiment that was projected by the Norwegian captain, Adolfo Andresen, developed between 1903 and 1904. Consisting of two incursions along the Patagonian-Fuegian archipelago, destined to the whaling and sealing, whaling experiment that used for the first time equipment of the modern whaling tradition, in Magallanes, Chile and the southern hemisphere. The sources used consist of a set of 37 texts published between 1894 and 1904 in the newspapers El Comercio and El Magallanes of Punta Arenas, and in addition, a series of 12 letters contained in the Mauricio Braun Archive, information that allows to fully characterize the itinerary of the ship, the preparation of the whaling operation and the details of the incursions, providing new information for the better knowledge of the local and national whaling culture.
Keywords: whaling; modern whaling tradition; harpoon cannon; adolfo andresen; braun & blanchard; punta arenas